Efficient enzyme supported on modified Mg(II) and Zn(II) layered double hydroxides as biocatalyst for enhanced synthesis of specialty ester - Abdul Rahman, Mohd Basyaruddin; Md Yunus, Noor Mona; Abdul Ghani, Noraini; Basri, Mahiran; Raja Abdul Rahman, Raja Noor Zaliha; Salleh, Abu Bakar (2007)
Wide variation in composition and properties of esters makes them one of the most important classes of organic compounds. They find widespread uses as perfumes, cosmetics, solvents, plasticizers, flavors, in medicine and in pharmaceutical industry (Foresti et al., 2005). As compared to the conventional ester synthesis using mineral acids as a catalyst, the use of free or immobilized enzymes as biocatalysts to produce esters offer many significant advantages and currently enzymes are an industrial feasible alternative to ester production processes (Aracil et al., 2006). In this study, lipase from Candida rugosa (CRL) was immobilized onto calcined layered double hydroxides (CLDH) via adsorption. LDH can be represented by the general formula [M2+(1-x) M3+x (OH)2]x+(An- x/n). mH2O where, M2+ is a divalent metal, M3+ is a trivalent metal, A n- is an interlayer anions and x is the stoichiometric coefficient which corresponds to the ratio of M2+/M3+. LDH of Mg/Al-NO3 (MAN) and Zn/Al-NO3 (ZAN) with molar ratio of M2+:Al3+= 4:1 were synthesized with co-precipitation method (Abdul Rahman et al., 2006). Thermal decompositions of MAN and ZAN were characterized with Thermogravimetry and Derivative Thermogravimetry Analyses (TG-DTG). From the LDHs’ thermal decomposition profile, weight loss of MAN and ZAN occurred essentially in four steps; i) dehydration, ii) dehydroxylation, iii) decomposition of interlayer anion and iv) collapse of the layered structure. Therefore, in order to enhance the surface area and the porosity of the LDH without altering the structure of the LDHs, calcinations of MAN, NAN and ZAN were done at 150oC. The properties of CLDHs (CMAN and CZAN) were characterized with Powder-X-Ray Diffraction (P-XRD), Scanning Electron Microscopy (SEM), Analysis of Particle Size Distributions and Analysis of Surface Area and Porosity (ASAP). CMAN and CZAN were then used as support for CRL. CMAN-CRL and CZAN-CRL prepared were characterized using Coomassie Blue dye protein staining-light microscopy analysis, Fourier Transform-Infra Red (FT-IR) and Scanning Electron Microscopy-Energy Dispersive X-Ray (SEM-EDX). P-XRD pattern, SEM images and ASAP results showed that the crystallinity and surface properties of LDH increased upon calcinations. The ASAP analysis showed higher BET surface area of resulted materials upon calcinations with CMAN (1.8m2/g to 18.8m2/g) and CZAN (8.5m2/g to 11.7m2/g). Both CMAN and CZAN exhibited good properties as enzyme supports with high protein adsorption (more than 70%), 3.52 mg protein/g and 2.02 mg protein/g, respectively. In the protein staining analysis using Coomassie Blue dye reagent, images of stained and then destained of CMAN-CRL and CZAN-CRL showed several blue spots around the CLDHs’ surfaces indicated that CRL was adsorbed onto CLDHs. In the FT-IR spectra of CMAN-CRL and CZAN-CRL, alkyl bands at 2928cm-1 (C-H), 1452cm-1 (N-H) and a broad band at 1200-1000cm-1 (C-O) verified CRL adsorption onto CLDHs. From SEM-EDX analysis, elements of CRL were detected in CMAN-CRL and CZAN-CRL prepared, confirmed that CRL was adsorbed onto CLDHs. CMAN-CRL and CZAN-CRL were then used as biocatalysts in synthesis of methyl caprylate, a short chain esters with fruity and orange-like or citrus odor which is important as flavor and aroma constituent in alcoholic beverages, puddings, soft candy and frozen dairy (Burdoch, 2005). High production of methyl caprylate was achieved using CMAN-CRL (70%) and CZAN-CRL (80%). The percentage of conversion for CLDHs-CRL turned out to be more than 10 times greater than it was when free CRL was used (6%), showed that immobilization of CRL onto CLDHs increased the biocatalytic activity of CRL and strongly suggested that CLDHs stabilized the enzyme for use in organic media.